1994
DOI: 10.1093/oxfordjournals.humrep.a138597
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the endogenous luteinizing hormone surge by the gonadotrophin-releasing hormone antagonist Cetrorelix during ovarian stimulation

Abstract: Surges of luteinizing hormone (LH) that result in luteinization but occur prematurely with respect to the diameter of the leading follicle, prevent attempts to induce multiple follicular maturation for in-vitro fertilization (IVF) in a significant number of women. We examined the possibility of blocking premature LH surges by the administration of Cetrorelix, a potent antagonist of gonadotrophin-releasing hormone (GnRH), in a study including 20 patients, some of whom had previously shown premature LH surges. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
113
0
14

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(131 citation statements)
references
References 0 publications
0
113
0
14
Order By: Relevance
“…Williams et al reported a cancellation rate of 0%; thus, proving the validity of a GnRH antagonist for IVF [3]. Several injection methods for a GnRH antagonist have been reported, such as a single 3-mg injection of a GnRH antagonist [8], or a daily injection of 0.25mg of a GnRH antagonist [4,7,9,10]. Although the number of retrieved oocytes is lower than that of the long-protocol method, which uses a GnRH agonist, there was no significant difference in the clinical pregnancy rate [3,11].…”
Section: Introductionmentioning
confidence: 99%
“…Williams et al reported a cancellation rate of 0%; thus, proving the validity of a GnRH antagonist for IVF [3]. Several injection methods for a GnRH antagonist have been reported, such as a single 3-mg injection of a GnRH antagonist [8], or a daily injection of 0.25mg of a GnRH antagonist [4,7,9,10]. Although the number of retrieved oocytes is lower than that of the long-protocol method, which uses a GnRH agonist, there was no significant difference in the clinical pregnancy rate [3,11].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of these agents in preventing premature LH surge has been demonstrated (1) . Several studies have also demonstrated that GnRH antagonists decrease the premature luteinization rates and cycle cancellation rates (12,13) .…”
Section: Premature Lh Surge and Pregnancy Ratesmentioning
confidence: 99%
“…Gonadotropin-releasing hormone (GnRH) antagonists have been recently introduced in clinical practice for ovarian stimulation in assisted reproduction cycles (1) .…”
Section: Introductionmentioning
confidence: 99%
“…LH plays a role in both oocyte maturation and ovulation through a mechanism which is poorly understood (1).Granulosa cells acquire LH receptors by the mid follicular phase of the menstrual cycle coinciding with a rise in LH level (2) and a premature LH surge may cause early luteinization and follicular atresia in cases of controlled ovarian stimulation (3) . High LH levels causes premature secretory transformation of the endometrium decreasing the chances of implantation and thereby decreasing pregnancy rates [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%